Relation between sum of 2mth powers and polynomials of triangular numbers - Mohamat Johari, Mohamat Aidil; Mohd Atan, Kamel Ariffin; Sapar, Siti Hasana (Pushpa Publishing House, 2014)
Let Ф (m, k)(n) denote the number of representations of an integer n as a sum of k 2mth powers and Ψ (m, k)(n) denote the number of representations of an integer n as a sum of k polynomial Pm(γ), where γ is a triangular number. We show that Ф (2, k)(8n + k) = 2k Ψ(2,k) (n) for 1 ≤ k ≤ 7. A general relation between the number of representations (formula presented) and the sum of its associated polynomial of triangular numbers for any degree m ≥ 2 is given as Ф(m, k) (8n + k) = 2k Ψ (m, k) (n).